ANALISIS FAKTOR YANG MEMPENGARUHI FOREIGN DIRECT INVESTMENT (FDI) ASING TERHADAP PERTUMBUHAN EKONOMI DI IDONESIA TAHUN 2000-2019 - Wulan Rahmawati (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
. This study aims to analyze the variables that affect Foreign Direct Investment (FDI), inflation, interest rates and exports to economic growth either partially or simultaneously. Indonesia is the fourth most populous country in the world with a large workforce and abundant natural resources. This makes Indonesia one of the most promising countries to invest in. This foreign investment opens up many new jobs so that the unemployment rate can be reduced. The most obvious benefit from the entry of foreign investment is to increase state revenues through taxes. In addition, it creates a more stable relationship in the economic sphere of the two countries. The data used in the form of secondary data, which is data obtained from the official website or website. Based on these objectives, the data analysis technique uses time series data analysis with the ECM (Error Correcton Model) model. A method for estimating the movement between long-term and short-term variables.